Dynamics of small grains in transitional discs - Krumholz, Mark R.; Ireland, Michael J.; Kratter, Kaitlin (Monthly notices of the Royal Astronomical Society, 2020)
Transitional discs have central regions characterized by significant depletion of both dust and gas compared to younger, optically thick discs. However, gas and dust are not depleted by equal amounts: gas surface densities are typically reduced by factors of ∼100, but small dust grains are sometimes depleted by far larger factors, to the point of being undetectable. While this extreme dust depletion is often attributed to planet formation, in this paper we show that another physical mechanism is possible: expulsion of grains from the disc by radiation pressure. We explore this mechanism using 2D simulations of dust dynamics, simultaneously solving the equation of radiative transfer with the evolution equations for dust diffusion and advection under the combined effects of stellar radiation and hydrodynamic interaction with a turbulent, accreting background gas disc. We show that, in transition discs that are depleted in both gas and dust fraction by factors of ∼100-1000 compared to minimum mass Solar nebular values, and where the ratio of accretion rate to stellar luminosity is low ($\dot{M}/L \lesssim 10^{-10}\, M_\odot$ yr$^{-1}\, L_\odot ^{-1}$), radiative clearing of any remaining ${\sim}0.5\, μ m$ and larger grains is both rapid and inevitable. The process is size-dependent, with smaller grains removed fastest and larger ones persisting for longer times. Our proposed mechanism thus naturally explains the extreme depletion of small grains commonly found in transition discs. We further suggest that the dependence of this mechanism on grain size and optical properties may explain some of the unusual grain properties recently discovered in a number of transition discs. The simulation code we develop is freely available.